Ultra-Early (<12 Hours) Surgery Correlates With Higher Rate of American Spinal Injury Association Impairment Scale Conversion After Cervical Spinal Cord Injury. Issue 2 (28th November 2018) - Burke, John F; Yue, John K; Ngwenya, Laura B; Winkler, Ethan A; Talbott, Jason F; Pan, Jonathan Z; Ferguson, Adam R; Beattie, Michael S; Bresnahan, Jacqueline C; Haefeli, Jenny; Whetstone, William D; Suen, Catherine G; et al.
Abstract: BACKGROUND: Cervical spinal cord injury (SCI) is a devastating condition with very few treatment options. It remains unclear if early surgery correlated with conversion of American Spinal Injury Association Impairment Scale (AIS) grade A injuries to higher grades. OBJECTIVE: To determine the optimal time to surgery after cervical SCI through retrospective analysis. METHODS: We collected data from 48 patients with cervical SCI. Based on the time from Emergency Department (ED) presentation to surgical decompression, we grouped patients into ultra-early (decompression within 12 h of presentation), early (within 12-24 h), and late groups (>24 h). We compared the improvement in AIS grade from admission to discharge, controlling for confounding factors such as AIS grade on admission, injury severity, and age. The mean time from injury to ED for this group of patients was 17 min. RESULTS: Patients who received surgery within 12 h after presentation had a relative improvement in AIS grade from admission to discharge: the ultra-early group improved on average 1.3. AIS grades compared to 0.5 in the early group ( P = .02). In addition, 88.8% of patients with an AIS grade A converted to a higher grade (AIS B or better) in the ultra-early group, compared to 38.4% in the early and late groups ( P = .054). CONCLUSION: These data suggest that surgical decompression after SCI that takes place within 12 h may lead to a relative improved neurological recovery compared to surgery that takes place after 12 h.